Trees & forests of America - Palmer, Tim, 1948- (New York : Abrams, 2008)
Trees & Forests of America is an unprecedented collection of 200 stunning photographs by award-winning author Tim Palmer. Along with breath-taking images, his expressive text celebrates the exquisite beauty of nature and explains why trees and forests are important to all life. In this remarkable volume of unaltered photos it is easy to get lost in sunbeams shining through green canopies or in the sky-reaching rise of the largest living organisms on earth.
The way to the woods -- Arboreal visions of wild America -- The life of a tree -- The nature of the forest -- Sylvania -- The Northern forest -- Central hardwoods and the Appalachians -- The South -- Rocky Mountains -- Drylands and deserts -- Sierra Nevada and Southern California -- The Northwest -- Alaska and Hawaii --Remnants and regrowth -- Seeing the trees and the forest.
Map on lining paper.
Includes bibliographical references and index.
Keywords: Palmer, Tim, -- 1948-; Photography of trees; Trees -- United States -- Pictorial works; Forests and forestry -- United States -- Pictorial works